1990
DOI: 10.1002/jmv.1890300114
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses in recipients of varicella vaccine assayed by immunoblotting

Abstract: Sera taken from 35 children with cancer who had been vaccinated with live varicella vaccine were assayed using immunoblotting for the presence of IgG class antibodies to proteins present in varicella-zoster virus (VZV)-infected cells. Sera from 23 of these patients were also assayed for IgM class antibodies. The patterns of immunoreactivity observed for these patients following vaccination were substantially weaker and more variable than those detected following natural VZV infection in otherwise healthy indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…19,[23][24][25][26] A previous study showed that an adjuvanted gE subunit vaccine candidate was well tolerated and more immunogenic than a live-attenuated VZV vaccine in young (18-30 years) and older (50-70 years) immunocompetent adults. 27 Here, we describe the results of a phase 1/2 clinical trial examining the safety and immunogenicity of this adjuvanted gE subunit candidate vaccine in adult autologous HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…19,[23][24][25][26] A previous study showed that an adjuvanted gE subunit vaccine candidate was well tolerated and more immunogenic than a live-attenuated VZV vaccine in young (18-30 years) and older (50-70 years) immunocompetent adults. 27 Here, we describe the results of a phase 1/2 clinical trial examining the safety and immunogenicity of this adjuvanted gE subunit candidate vaccine in adult autologous HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that VZV glycoproteins induce strong humoral responses both in naturally infected individuals and in varicella vaccine recipients [Dubey et al, 1988;Harper et al, 1990;Watson et al, 1994]. Although antibodies to the three major glycoproteins have been assayed [Brunell et al 1987;LaRussa et al 1990], the relative contribution of the two main glycoproteins, gE and gB, to neutralizing antibody titers has never been established.…”
Section: Discussionmentioning
confidence: 98%
“…gE, with an Mr of 90-98 kDa, is the most abundant and immunogenic gp and is the predominant gp in VZV-infected human cell membranes [Keller et al, 1984;Montalvo and Grose, 1987;Dubey et al, 1988]. Anti-gE antibody has been demonstrated in subjects with recent primary infection, in subjects vaccinated with the live VZV-Oka vaccine [Harper et al, 1990], and in subjects known to have been infected with VZV in the past [Dubey et al, 1988]. The avidity of IgG antibodies has been shown to increase during the months following primary infection as well as after zoster [Kangro et al, 1991].…”
Section: Introductionmentioning
confidence: 98%
“…However, 81·5% of HZ/su recipients in the Phase III study experienced pain at the site of injection and 66% of recipients had mild to moderate systemic reactions (grade 3 severity in 11·4% of the subjects) such as myalgia (most common), fatigue and headache . Glycoprotein E was selected for this subunit vaccine because it is the most abundant viral glycoprotein, and also elicits specific CD4 T cell responses . The adjuvant being used is ASO1, which is a liposome‐based adjuvant system containing 3‐O‐desacyl‐4′‐monophosphoryl and saponin QS‐21, which activates the Toll‐like receptor (TLR)‐4 pathway and stimulates both antibody and T helper type 1 (Th1) responses .…”
Section: Vaccines Against Herpes Zostermentioning
confidence: 99%